2019
DOI: 10.1590/fst.15418
|View full text |Cite
|
Sign up to set email alerts
|

The compound, diallyl disulfide, enriched in garlic, prevents the progression of doxorubicin-induced nephropathy

Abstract: The main medicinal property of garlic is mostly attributed to its organosulfur compounds, of which the oil-soluble diallyl disulfide (DADS) is the principal component of distilled garlic oil. Nuclear factor erythroid 2-related factor 2 (Nrf2) is an important cellular regulator in response to oxidative stress. This study assessed the possible protective effect of DADS on doxorubicin (Dox)-induced nephrotoxicity and its potential regulation of the Nrf2 pathway. Treatment with DADS (200 μM) induced heme oxygenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…With the addition of 2% black garlic powder, nuggets had the lowest TPC, followed by BHT and 1% black garlic powder. The lower total microbial nuggets were caused by the antimicrobial content in black garlic such as phenolic compounds (including phenolic acids and flavonoids) (Papuc et al, 2017b), β-carbolines alkaloids (Cao et al, 2007), melanoidins (Wang et al, 2011), organic acids and organic sulfur compound (Yin & Cheng, 2003;Lin et al, 2019). Botas et al (2019) reported that black garlic has antimicrobial activity against gram-positive and gram-negative bacteria.…”
Section: Total Plate Countmentioning
confidence: 99%
See 1 more Smart Citation
“…With the addition of 2% black garlic powder, nuggets had the lowest TPC, followed by BHT and 1% black garlic powder. The lower total microbial nuggets were caused by the antimicrobial content in black garlic such as phenolic compounds (including phenolic acids and flavonoids) (Papuc et al, 2017b), β-carbolines alkaloids (Cao et al, 2007), melanoidins (Wang et al, 2011), organic acids and organic sulfur compound (Yin & Cheng, 2003;Lin et al, 2019). Botas et al (2019) reported that black garlic has antimicrobial activity against gram-positive and gram-negative bacteria.…”
Section: Total Plate Countmentioning
confidence: 99%
“…Not only as antioxidant agents, black garlic also act as antimicrobials (Altuntas & Korukluoglu, 2019). Black garlic contain phenolic compound, β-carbolines alkaloids (Cao et al, 2007), melanoidins (Wang et al, 2011), organic acids and organic sulfur compound (Yin & Cheng, 2003;Lin et al, 2019). According to Arslaner (2020) organic sulfur compound decrease the yeast-mould compared to the control.…”
mentioning
confidence: 99%
“…The statistical analysis was done by using SPSS software version 25. One-way analysis of variance was applied followed by Tukey Kramer multiple comparison post-hoc test as analyzed by Lin et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…DADS can also reduce oxidative stress and inflammation by inhibiting CYP2E1 and NF-κB, thereby reducing the toxic effect of AAP on rat kidneys . In an animal study, pretreatment with DADS increases catalase activity through the Nrf2 pathway and so reduces kidney toxicity induced by Dox-induced oxidative stress in mice . Moreover, the use of DAS prevents renal peroxidation damage of ROS caused by CP administration .…”
Section: Biological Functions Of Sulfur-containing Spice Compoundsmentioning
confidence: 99%